EXPLORATORY FACTOR ANALYSIS OF TPACK IN THE CONTEXT OF ESL SECONDARY SCHOOL TEACHERS IN SABAH - Ahmad Abdul Rauf; Suyansah Swanto; Syahrul Nizam Salam, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The aim of this study was to adapt the Survey of EFL-Technological Pedagogical Content Knowledge (EFL-TPACK) by BostancÄ±oÄŸlu & Handley (2018) and to investigate its factor structure through exploratory factor analysis. 100 ESL teachers of secondary schools in Sabah participated in this study. SPSS application has been used for statistical analyses. The reliability of the subscales from Cronbach Alpha is ranging from 0.898 to 0.902. The final TPACK survey included a total of 33 items: 6 TK, 3 CK, 6 PK/PCK, 6 TCK, 6 TPK, and 6 TPACK. Based on the findings also, the TPACK Survey has been found to be ideal to study on TPACK level of English language teachers in Malaysia.